Shear Resistance Contribution of Constituent Elements Consisting RCS Joint - Eun-Jin Lee; Jeong-Ho Moon; Moon-Sung Lee (Advances in Civil Engineering)
In this study, constituent elements affecting the shear strength of RCS joints were investigated through experiment and analysis study. A series of five interior RCS beam-column joint specimens, which were classified as JH-type and CP-type, was tested to investigate the contribution of each shear resisting element such as JH (Joint Hoop), CP (Cover Plate), FBP (Face Bearing Plate), E-FBP (Extended Face Bearing Plate), TB (Transverse Beam), and BP (Band Plate). Comparison between experiment and analysis results showed that the stiffness and strength of the RCS joint were reasonably assessed from the analysis. As a result of the analysis, it was found that TB, E-FBP, and CP increased the shear strength by about 15%, 14%, and 26%, respectively. For the JH-type specimen, 70% of the shear strength of the RCS joint is supported by the inner element and 30% of the shear strength is supported by the outer element. Shear strength contribution ratio of the outer element of CP-type specimen is larger than that of the JH-type specimen. For all specimens except for SNI-1, around 10% of total shear strength is supported by FBP. The shear strength equation of the RCS joint proposed by ASCE underestimates the contribution of the outer element, while that of M-Kanno tends to overestimate it.